Pengaruh Islamic Social Reporting terhadap Profitabilitas (Return on Asset dan Return on Equity) Pada Bank Umum Syariah di Indonesia - Santika, Ana (Universitas Muhammadiyah Malang, 2019)
The act of accuracy and prudence is very important in the company because is the factor that determines the sustainability of companies such as banking. This study aims to analyze the effect of Shariah Complaints towards the profitability of Islamic Banks in Indonesia. This research is quantitative using documentation method and library study in data collection. The sampling technique uses purposive sampling with the criteria of Islamic commercial banks that publish annual-reports from 2013 to 2017 from 13 Islamic commercial banks (BUS) in Indonesia. The results of this study show that the Funding and Investment, Products and Services, Employees, Community or Social, Environmental, Corporate Governance simultaneously does not have influence significantly the ROE variable, but it does significantly influence ROA. This means that the wider the Islamic social reporting of Islamic banking, the greater the profitability of Islamic banking. In addition, high profitability will encourage managers to provide more detailed information, because they want to convince investors of company profits and its compensation for management.